2012
DOI: 10.1177/089875641202900304
|View full text |Cite
|
Sign up to set email alerts
|

Common Dental Disorders of the Degu (Octodon Degus)

Abstract: Dental disease is prevalent in the captive degu (Octodon degus), yet little has been documented on the variety of disorders in this species. In this internet-based study, dental cases presented over a 7-year period were collated, analyzed, and grouped. Of the 137 total cases, the most common dental disorder of the degu was found to be molar malocclusion (42.3 %). Other disorders documented included enamel decoloration (13.1%), molar elodontoma (8.0%), enamel hypoplasia (6.6%), incisor tooth fracture (6.6%), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
(66 reference statements)
4
13
1
Order By: Relevance
“…This supports the theory that cheek teeth malocclusion can lead to incisor malocclusion and vice versa. 2 Cheek teeth malocclusion was also related to apical cheek teeth elongation. In rabbits, it was observed that elongated apices were always the irst sign, and sometimes the only sign, of acquired dental disorders.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This supports the theory that cheek teeth malocclusion can lead to incisor malocclusion and vice versa. 2 Cheek teeth malocclusion was also related to apical cheek teeth elongation. In rabbits, it was observed that elongated apices were always the irst sign, and sometimes the only sign, of acquired dental disorders.…”
Section: Discussionmentioning
confidence: 98%
“…This necessity for recurrent dental treatment was much higher than found in another study (24.1%, n=58). 2 In the current study, degus with known dental disorders were monitored at regular intervals. Of degus with dental disorders, 37.6 per cent was euthanased because of returning dental abnormalities and deteriorating health and body condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps these data could be related to the older age of the examined animals (mean age 6 ± 1.9 years) vs. 2.3 ± 1.86 years in previous studies on pet degus [5], or because some of the animals of our study were referred to the university clinic for surgery. To date, different neoplastic lesions have been described in this species (cutaneous lipoma, melanoma, myxosarcoma, malignant histiocytoma, fibrosarcoma, cervical lymphosarcoma, hepatoma, hepatocellular carcinoma, splenic hemangioma, bronchioalveolar carcinoma, renal transitional cell carcinoma, renal choristoma, elodontoma, uterine angioleiomyoma, vaginal leiomyosarcoma, parathyroid adenocarcinoma, pulmonary adenocarcinoma and coccygeal chordoma) [6][7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of degus diseases are rare and the incidence of neoplasia appears to be low [5]. Other than single case reports [6][7][8][9][10][11][12][13], seven neoplasms were detected in 189 animals [14] and six tumours were described in another study performed in 300 degus [5]. To date, no reports about non-neoplastic proliferative lesions in degus have been reported.…”
Section: Introductionmentioning
confidence: 99%